The Worthiness of Bahasa Indonesia Supplement Book as Learning Support Textbook in SMA/SMK - Rahayu, Fitri Itut; Nasucha, Yakub; Rahmawati, Laili Etika (Universitas Muria Kudus, 2023)
As material that has been prepared in the context of learning, the main textbook should have the feasibility so that it is able to carry out tasks in the world of education according to the field and level of the book. Likewise with supplementary textbooks. At this time, there will be many supplement books that are actually able to help students and educators in interacting and collaborating today. Quality textbooks are able to become adequate learning materials for students to more easily reach certain levels of Basic Competence. Textbooks are able to make students more independent in learning the substance and method. (Puskurbuk, 2012). Textbooks are able to direct students to independently access learning materials without the full help of educators. The purpose of this study is to describe the feasibility of two Indonesian supplementary textbooks used at SMKN 2 Wonogiri, namely the YW book and the E book. This research is a qualitative descriptive type with content analysis method. This study has two sources of data in the form of primary data and secondary data. The content, both content and language of the YW and E books, is primary data, while secondary data is the result of interviews with Indonesian language teachers and student questionnaires for class XII as supporting data in the study. Secondary data is used as a comparison of primary data. Testing the validity of the data using source triangulation. The results of the study stated that the Indonesian supplementary text books used at SMKN 2 Wonogiri, namely the YW book and the E book had linguistic, content, presentation, and graphic feasibility. The two supplementary books mentioned above are suitable for use at SMKN 2 Wonogiri.As material that has been prepared in the context of learning, the main textbook should have the feasibility so that it is able to carry out tasks in the world of education according to the field and level of the book. Likewise with supplementary textbooks. At this time, there will be many supplement books that are actually able to help students and educators in interacting and collaborating today. Quality textbooks are able to become adequate learning materials for students to more easily reach certain levels of Basic Competence. Textbooks are able to make students more independent in learning the substance and method. (Puskurbuk, 2012). Textbooks are able to direct students to independently access learning materials without the full help of educators. The purpose of this study is to describe the feasibility of two Indonesian supplementary textbooks used at SMKN 2 Wonogiri, namely the YW book and the E book. This research is a qualitative descriptive type with content analysis method. This study has two sources of data in the form of primary data and secondary data. The content, both content and language of the YW and E books, is primary data, while secondary data is the result of interviews with Indonesian language teachers and student questionnaires for class XII as supporting data in the study. Secondary data is used as a comparison of primary data. Testing the validity of the data using source triangulation. The results of the study stated that the Indonesian supplementary text books used at SMKN 2 Wonogiri, namely the YW book and the E book had linguistic, content, presentation, and graphic feasibility. The two supplementary books mentioned above are suitable for use at SMKN 2 Wonogiri.